The - Liddle, Andrew R.
Lavishly illustrated with almost two hundred halftones and diagrams, The Oxford Companion to Cosmology offers readers an engaging, state-of-the-art reference work on modern cosmology, the only such resource presently available. In more than 350 in-depth entries, Andrew Liddle and Jon Loveday--two authorities on theoretical and experimental cosmology--cover the entire scope of this cutting-edge field, from cosmic rays and dark energy to Higgs boson and neutrinos. Beginning with an introductory essay on Hot Big Bang Cosmology, the Companion illuminates the ideas behind our current understanding of the universe, outlines some of the fundamental physics from which those ideas emerge, and discusses the many strands of observational evidence available to the modern cosmologist. The authors tackle such fascinating topics as anti-matter, the age of the universe, black holes, quasars, radio galaxies, Superstring theory, and WIMPs (weekly interacting massive particles). The book also features biographical profiles of major scientists, from Arthur Eddington and Albert Einstein to George Gamow and Edwin Hubble, and informative entries on the tools of exploration such as the Cosmic Background Explorer satellite, the Hubble Space Telescope, and the Keck Observatory. Extensive cross-referencing allows readers to pursue ideas throughout the book, and web links direct the reader to recommended online resources